Exploring sustainable food choices among adults in the United Arab Emirates: a cross-sectional study - Cheikh Ismail, Leila; Hashim, Mona; Osaili, Tareq M.; Faris, MoezAlIslam E.; Naja, Farah; Radwan, Hadia; Hasan, Fayeza; Saleh, Sheima T.; Al Rajaby, Radhiya; Al Daour, Rameez; Stojanovska, Lily; Al Dhaheri, Ayesha S.; et al. (Frontiers in Sustainable Food Systems, 2023)
Introduction Dietary choices serve as a vital and ongoing link between environmental sustainability and human health. This study aimed to assess the consumption behavior of people in the United Arab Emirates (UAE) concerning sustainability and determine factors that contribute to sustainable food choices. Methods A cross-sectional, web-based study was conducted among adults in the UAE (n = 1,113). Data on participants’ sociodemographic characteristics, attitudes toward sustainable food choices, and reasons behind sustainable food choices were collected. Independent t-test and one-way ANOVA tests were used to investigate the differences in the level of agreement to nine statements about sustainable food choices among different sociodemographic groups on a scale of 1–5 ranging from strongly disagree to strongly agree. Participants’ responses to open-ended questions were filtered and clustered into eight different categories and presented as counts and percentages. Results and discussion Participants agreed on trying new healthy and environmentally friendly foodstuff (3.57 ± 1.04). Females (p = 0.002) and older adults (>50 years; p = 0.001) showed higher agreement with avoiding red meat. Older participants, and those with higher education (p = 0.020 and p < 0.001, respectively) showed higher agreement with favoring plant-based diets. 21.2% reported avoiding red meat and 23.1% preferred a plant-based diet. Of those who favored plant-based food the main reported reason was ‘health and nutritive value’ (66.5%), while of those who avoided red meat, preference was the most reported reason (41.9%). Although the study sample did not greatly adopt sustainable food choices, they leaned toward trying environmentally friendly foods. Females, older adults, and highly educated people aligned themselves with more sustainable food choices. Targeted policies and the integration of sustainability aspects within dietary guidelines to promote healthy, sustainable, and affordable diets are needed.